Enhancing 21st-Century Learning: The Impact of Gamification with Quizwhizzer on English Language Vocabulary Acquisition - Dohny, Queencie; Soekarno, Megawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the realm of 21st-century learning, the integration of digital tools like Kahoot! and Quizizz has ushered in an era of interactive learning experiences; particularly in enhancing students' acquisition of English language vocabulary. However, amidst the proliferation of digital tools in education, there arises a necessity for diverse platforms. Therefore, this study aims to assess the efficacy of incorporating Quizwhizzer application as a gamification tool within the educational landscape. This study employs the Quizwhizzer application to investigate the impact of gamification approach on the English language vocabulary performance of 42 Pre-university students. The participants' English language vocabulary scores are subjected to be analysed using quasi-experimental design. The findings show students’ notable improvement with the inclusion of gamification method, with effect size of 1.223 indicated a large effect size. This study's findings underscore that Quizwhizzer, akin to Kahoot! and Quizizz, serves as an effective gamification tool for enhancing students' performance in English language vocabulary.